Effect of alcoholism against the SARS-Cov2-Covid-19 VIRUS - Sánchez Lorenzo Nora Guadalupe; Torres Sabino Mitzi Guadalupe; Vargas Cabrera Yeraldin; Reynoso Vázquez Josefina; Olga Rocío Flores Chávez; López Zermeño María del Carmen; Leticia Carolina Hernández Esparza; Pedro Negrete Rivera; Julieta Alelí Izquierdo Vega; Miguel Ángel Serna Martinez; et al. (Public Health, 2026)
Alcoholism, a condition characterized by excessive and prolonged alcohol consumption, has numerous adverse health effects, which are exacerbated in the context of the SARS-CoV-2 pandemic. The relationship between alcohol consumption and susceptibility to COVID-19 is complex and multifaceted. First, alcohol weakens the immune system, reducing the body’s ability to fight infections, which increases the risk of contracting severe respiratory illnesses such as COVID-19. Furthermore, chronic alcohol consumption can lead to underlying medical conditions, such as liver and cardiovascular diseases, which are known risk factors for developing severe COVID-19 complications. The behavior of people with alcoholism also contributes to a higher risk of exposure to the virus. People who abuse alcohol may have reduced adherence to preventive measures, such as social distancing and mask use, thus increasing the likelihood of infection. Likewise, alcohol consumption in public places or at social gatherings increases the probability of virus transmission. During the pandemic, stress and anxiety have led to increased alcohol consumption in some populations, exacerbating mental and physical health problems. This increase can create a vicious cycle where alcohol consumption and the risk of COVID-19 infection negatively reinforce each other.